Urban growth and evolution of public space in the city of Manizales, Colombia. - Ortega Sapuyes, Juan Felipe (2022)
Most cities evolves and expand urban and demographically over time, which leads to think of new dynamics of urban growth from what is known, without forgetting the importance of public space in the image and development of a city. The objective of this research is to contrast the urban growth of the city of Manizales, Colombia by periods from its foundation to the present, based on the relationship between public space area, number of inhabitants and urbanized area. Using a geographic information system (GIS) with the free software QGIS, cartography was compiled and processed together with photographs and data layers for each period, to analyze the urban form, public space, urban density and population increase. Nine time periods were identified, from 1848 to 2021, in which a constant effective growth of urban form and public space was evidenced until the period 1993-2008, along with a gradual decrease in population density recorded since the founding of the city. So far, no urban studies have been found that contrast population growth and its relationship with the public space of the city of Manizales, preventing new visions of the historical evolution from its founding date to the present.